Sex differences in chronic pain-induced mental disorders: Mechanisms of cerebral circuitry - Shen, Zuqi; Li, Wei; Chang, Weiqi; Yue, Na; Yu, Jin (Frontiers in Molecular Neuroscience, 2023)
Mental disorders such as anxiety and depression induced by chronic pain are common in clinical practice, and there are significant sex differences in their epidemiology. However, the circuit mechanism of this difference has not been fully studied, as preclinical studies have traditionally excluded female rodents. Recently, this oversight has begun to be resolved and studies including male and female rodents are revealing sex differences in the neurobiological processes behind mental disorder features. This paper reviews the structural functions involved in the injury perception circuit and advanced emotional cortex circuit. In addition, we also summarize the latest breakthroughs and insights into sex differences in neuromodulation through endogenous dopamine, 5-hydroxytryptamine, GABAergic inhibition, norepinephrine, and peptide pathways like oxytocin, as well as their receptors. By comparing sex differences, we hope to identify new therapeutic targets to offer safer and more effective treatments.